Remittances in a Dynamic Gobal Landscape : Methodologies, Implications, and Emerging Challenges - Procházková Iliniţchi, Cristina (2024)
ILINITCHI PROCHÁZKOVÁ, C. Remittances in a Dynamic Gobal Landscape: Methodologies, Implications, and Emerging Challenges. VŠE, NAKLADATELSTVÍ OECONOMICA, 2024, 237 S.